The Impact of the Right to Information Act on Administrative Accountability - Dasari, Sairam (International Journal of Psychosocial Rehabilitation, 2020)
The Right to Information (RTI) Act, 2005 is considered to be a significant legislation which has revolutionized the governance of India by changing the attitude of government from secrecy to transparency. The Act, by providing citizens with the legal right to access information possessed by public authorities, enables people to keep an eye on the actions of the government and to demand accountability for the actions and performance of public officials. This mechanism is a key element of the good governance and helps to curb corruption and promote participative democracy by making information public, which helps to reveal administrative malfeasance. But the operation of the Act is hampered by several constraints such as bureaucratic resistance, less trained Public Information Officers (PIOs) and less systematic record management infrastructure. Moreover, exemption clauses are frequently used inappropriately, appeals are pending in Information Commissions for long periods, and information seekers are frequently threatened with regard to the safety of their information. Institutional reforms, stronger awareness among rural population and incorporation of digital technology to facilitate information dissemination are all suggested as being crucial for the full realization of the potential of the RTI regime.